Efficacy and safety of first-line immunotherapy-containing regimens compared with chemotherapy for advanced or metastatic urothelial carcinoma: a network meta-analysis of randomized controlled trials - Liang, Weiming; Huang, Shibo; Huang, Yanping; Huang, Miaoyan; Li, Chunyan; Liang, Yiwen; Pang, Li (Frontiers in Oncology, 2024)
IntroductionTo assess the efficacy and safety of first-line immunotherapy-containing regimens compared with chemotherapy for advanced or metastatic urothelial carcinoma (UC).MethodA comprehensive search was performed in four databases (Pubmed, Embase, Web of Science, and the Cochrane Library) to identify randomized controlled trials (RCTs) assessing the efficacy of first-line immunotherapy-containing regimens for advanced or metastatic UC. The search encompassed the time span from the inception of the databases to April 23, 2024. A network meta-analysis (NMA) was conducted to assess the rates of progression-free survival (PFS), overall survival (OS), complete response (CR), objective response rate (ORR), and grade ≥ 3 adverse events (AEs).ResultsWe conducted a comprehensive analysis of five randomized controlled trials (RCTs) that included a total of 4749 patients. Nine different treatment regimens included in the study were ranked statistically and intuitively using NMA. The top five effective regimens, ranked by OS, were EV + Pembro (1.000), Nivol + Chemo (0.724), Atezo + Chemo (0.610), Durva + Treme (0.558), and Pembro + Chemo (0.530). The top five effective regimens, ranked by PFS, were EV + Pembro (0.999), Nivol + Chemo (0.640), Pembro + Chemo (0.484), Atezo + Chemo (0.373) and Chemo (0.003). The top five effective regimens, ranked by CR, were EV + Pembro (0.969), Nivol + Chemo (0.803), Atezo + Chemo (0.772), Pembro + Chemo (0.472), Durva + Treme (0.449). The top five effective regimens, ranked by ORR, were EV + Pembro (0.995), Nivol + Chemo (0.852), Pembro + Chemo (0.761), Atezo + Chemo (0.623), and Chemo (0.519).ConclusionOur results indicated that EV + Pembro as first-line therapy resulted in considerably improved efficacy and safety compared to chemotherapy for advanced or metastatic UC. ICI plus chemotherapy as first-line treatment resulted in a longer PFS, a greater ORR, but no longer OS compared to chemotherapy alone, as well as higher toxicity. ICI alone as first-line therapy provided similar OS and lower toxicity compared to chemotherapy, but lower ORR.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024538546.